A study on factors of personality traits that lead to employees’ job performance at Tenaga Nasional Berhad / Faridatul Avinash Ahmad Rozali - Ahmad Rozali, Faridatul Avinash (2014)
The objective of this study was to determine the relationship of personality traits (extraversion, neuroticism, openness to experience, agreeableness and conscientiousness) towards employees’ job performance at Tenaga Nasional Berhad, Muar. The employees’ of Tenaga Nasional Berhad Muar were used as respondents for this study. A field survey was conducted at Tenaga Nasional Berhad Muar to determine the influence of the dimension of personality traits on employees’ job performance. A total of 110 questionnaires were distributed to the employees and 110 were usable for data analyses. Demographic background was analyzed using Frequency Analysis. Descriptive Analysis was applied on the main variables of the study. Using Reliability Analysis, all items in the survey were found to be reliable. Pearson Correlation Analysis showed that only extraversion, openness to experience, agreeableness and conscientiousness were positively correlated with the dependent variable (employees’ job performance). Multiple Regression Analysis result indicates that openness to experience and conscientiousness was the strongest variable for lead to employees’ job performance